Plan for success: drafting effective hydrocarbon lifting provisions using the AIPN Model Joint Operating Agreement. (28th July 2018) - Fowler, Reg
ABSTRACT: The recent and relatively sustained rise in oil prices has given rise to renewed optimism in the sector. Hitherto shelved development projects could be back on the agenda, and exploration companies could be looking forward to the mechanics of lifting and disposing of produced hydrocarbons for the first time in a long while. A timely reminder of how to do so effectively is likely to be welcome. Article 9 of the AIPN 2012 Model International Joint Operating Agreement (JOA), the most widely used of all international form JOAs, addresses the disposition of hydrocarbon production in the production phase of a commercial discovery. Parties negotiating the JOA at the outset of a petroleum joint venture may find it difficult to adapt Article 9 in a practical way which provides for the evacuation of hydrocarbons in a success case which at the time of negotiation, will seem like a 'nice problem to have'. This article analyses Article 9 in detail, looking at each alternative in the light of the AIPN Model Crude Oil Lifting Agreement and the author's experience in drafting and negotiating lifting agreements for remote and underdeveloped hydrocarbon regions.